Self-Assembled Lecithin/Chitosan Nanoparticles Based on Phospholipid Complex: A Feasible Strategy to Improve Entrapment Efficiency and Transdermal Delivery of Poorly Lipophilic Drug - Dong W (Dove Medical Press, 2020)
Wujun Dong1,2 ,* Jun Ye1,2 ,* Weijue Wang,1,2 Yanfang Yang,1,2 Hongliang Wang,1,2 Tong Sun,1,2 Lili Gao,1,2 Yuling Liu1,2 1State Key Laboratory of Bioactive Substance and Function of Natural Medicines, Institute of Materia Medica, Chinese Academy of Medical Sciences & Peking Union Medical College, Beijing 100050, People’s Republic of China; 2Beijing Key Laboratory of Drug Delivery Technology and Novel Formulation, Institute of Materia Medica, Chinese Academy of Medical Sciences & Peking Union Medical College, Beijing 100050, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yuling LiuState Key Laboratory of Bioactive Substance and Function of Natural Medicines, Institute of Materia Medica, Chinese Academy of Medical Sciences & Peking Union Medical College, Beijing 100050, People’s Republic of ChinaTel +86 10 89285188Fax +86 10 89285190Email ylliu@imm.ac.cnPurpose: Lecithin/chitosan nanoparticles have shown great promise in the transdermal delivery of therapeutic agents. Baicalein, a natural bioactive flavonoid, possesses multiple biological activities against dermatosis. However, its topical application is limited due to its inherently poor hydrophilicity and lipophilicity. In this study, the baicalein-phospholipid complex was prepared to enhance the lipophilicity of baicalein and then lecithin/chitosan nanoparticles loaded with the baicalein-phospholipid complex were developed to improve the transdermal retention and permeability of baicalein.Methods: Lecithin/chitosan nanoparticles were prepared by the solvent-injection method and characterized in terms of particle size distribution, zeta potential, and morphology. The in vitro release, the ex vivo and in vivo permeation studies, and safety evaluation of lecithin/chitosan nanoparticles were performed to evaluate the effectiveness in enhancing transdermal retention and permeability of baicalein.Results: The lecithin/chitosan nanoparticles obtained by the self-assembled interaction of chitosan and lecithin not only efficiently encapsulated the drug with high entrapment efficiency (84.5%) but also provided sustained release of baicalein without initial burst release. Importantly, analysis of the permeation profile ex vivo and in vivo demonstrated that lecithin/chitosan nanoparticles prolonged the retention of baicalein in the skin and efficiently penetrated the barrier of stratum corneum without displaying skin irritation.Conclusion: These results indicate the potential of drug-phospholipid complexes in enhancing the entrapment efficiency and self-assembled lecithin/chitosan nanoparticles based on phospholipid complexes in the design of a rational transdermal delivery platform to improve the efficiency of transdermal therapy by enhancing its percutaneous retention and penetration in the skin.Keywords: lecithin/chitosan nanoparticles, transdermal delivery, phospholipid complex, baicalein